2020
DOI: 10.1136/annrheumdis-2020-eular.634
|View full text |Cite
|
Sign up to set email alerts
|

Thu0368 rapid Skin Thickness Progression Rate Is Associated With High Incidence Rate of Cardiopulmonary Involvement and Mortality in Patients With Early Diffuse Cutaneous Systemic Sclerosis (Dcssc)

Abstract: Background:There has been no prior inception cohort study regarding the incidence rate of cardiopulmonary involvement in patients with early dcSSc comparing among different groups of skin thickness progression rate.Objectives:The aims of this study were to compare differences in early dcSSc patients, which were classified into 3 subgroups; (a) rapid skin progression [RPsp], (b) intermediate skin progression [IMsp], and (c) slow skin progression [SLsp]; regarding: (1) clinical characteristics,(2) incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2011, Robyn T Domsic et al [5] reported that rapid skin fibrosis could be a predictor of mortality and early internal organ involvement in dsSSc. While 2020 S. Wangkaew et al [13] found that rapid skin fibrosis was associated with high cardiopulmonary complications incidence in patients with early dsSSc. Rapid skin fibrosis and internal organ involvement severity and rate determines the optimal therapeutic interventions for SSc [7].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Robyn T Domsic et al [5] reported that rapid skin fibrosis could be a predictor of mortality and early internal organ involvement in dsSSc. While 2020 S. Wangkaew et al [13] found that rapid skin fibrosis was associated with high cardiopulmonary complications incidence in patients with early dsSSc. Rapid skin fibrosis and internal organ involvement severity and rate determines the optimal therapeutic interventions for SSc [7].…”
Section: Discussionmentioning
confidence: 99%